Sustained Beneficial Effects of a Protocolized Treat‐to‐Target Strategy in Very Early Rheumatoid Arthritis: Three‐Year Results of the Dutch Rheumatoid Arthritis Monitoring Remission Induction Cohort. Issue 8 (26th July 2013) - Vermeer, M.; Kuper, H. H.; Moens, H. J. Bernelot; Drossaers‐Bakker, K. W.; van der, A. E.; van, P. L. C. M.; van de, M. A. F. J.
<x xml:space="preserve">Abstract</x> Objective Treat‐to‐target (T2T) leads to improved clinical outcomes in early rheumatoid arthritis (RA). The question is whether these results sustain in the long term. Our objective was to investigate the 3‐year results of a protocolized T2T strategy in daily clinical practice. Methods In the Dutch Rheumatoid Arthritis Monitoring remission induction cohort, patients newly diagnosed with RA were treated according to a T2T strategy aimed at remission (Disease Activity Score in 28 joints [DAS28] <2.6). Patients were treated with methotrexate, followed by the addition of sulfasalazine, and exchange of sulfasalazine with anti–tumor necrosis factor α agents in case of failure. Primary outcomes were disease activity, Health Assessment Questionnaire (HAQ) score, Short Form 36 physical component summary (PCS) and mental component summary (MCS) scores, and the Sharp/van der Heijde score (SHS) after 3 years. Secondary outcomes were sustained DAS28 remission (≥6 months) and remission according to the provisional American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) definition. Results After 3 years (n = 342), 61.7% of patients were in DAS28 remission and 25.3% met the provisional ACR/EULAR definition of remission. Sustained remission was experienced by 70.5%, which in the majority was achieved with conventional disease‐modifying antirheumatic drugs only. The median scores were 0.4 (interquartile range [IQR] 0.0–1.0) for the HAQ, 45.0 (IQR 38.4–53.2) for the PCS, 53.1 (IQR 43.2–60.8) for the MCS, and 6.0 (IQR 3.0–13.0) for the total SHS. Conclusion In very early RA, T2T leads to high (sustained) remission rates, improved physical function and health‐related quality of life, and limited radiographic damage after 3 years in daily clinical practice.